2023
DOI: 10.1101/2023.09.14.23295566
|View full text |Cite
Preprint
|
Sign up to set email alerts
|

bistro: An R package for vector bloodmeal identification by short tandem repeat overlap

Zena Lapp,
Lucy Abel,
Judith Mangeni
et al.

Abstract: 1. Measuring vector-human contact in a natural setting can inform precise targeting of interventions to interrupt transmission of vector-borne diseases. One approach is to directly match human DNA in vector bloodmeals to the individuals who were bitten using genotype panels of discriminative short tandem repeats (STRs). Existing methods for matching STR profiles in bloodmeals to the people bitten preclude the ability to match most incomplete profiles and multi-source bloodmeals to bitten individuals. 2. We dev… Show more

Help me understand this report
View published versions

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
2
1

Citation Types

0
6
0

Year Published

2024
2024
2024
2024

Publication Types

Select...
1
1

Relationship

1
1

Authors

Journals

citations
Cited by 2 publications
(6 citation statements)
references
References 16 publications
(21 reference statements)
0
6
0
Order By: Relevance
“…However, despite these limitations we were still able to estimate the maximum human-to-mosquito transmission efficiency to be between 0.14-0.27, which aligns with what has been observed in direct- and membrane-feeding experiments (11, 67, 68). Second, we could not match all mosquito STR profiles to people; however, our ability to incorporate a portion of incomplete and multisource profiles into our analysis increased our sample size by 37% (28), allowing us to more accurately use the matched bloodmeals and human infection data to estimate potential contributions to the transmission reservoir of different groups of people.…”
Section: Discussionmentioning
confidence: 99%
See 2 more Smart Citations
“…However, despite these limitations we were still able to estimate the maximum human-to-mosquito transmission efficiency to be between 0.14-0.27, which aligns with what has been observed in direct- and membrane-feeding experiments (11, 67, 68). Second, we could not match all mosquito STR profiles to people; however, our ability to incorporate a portion of incomplete and multisource profiles into our analysis increased our sample size by 37% (28), allowing us to more accurately use the matched bloodmeals and human infection data to estimate potential contributions to the transmission reservoir of different groups of people.…”
Section: Discussionmentioning
confidence: 99%
“…Mosquito bloodmeals were matched to cohort participants using the bistro R package (v0.2.0; (28)), which can provide matches for incomplete STR profiles and bloodmeals derived from multiple human sources. Briefly, matches based on weight-of-evidence likelihood ratios were determined for each mosquito-human pair and individual mosquito-based thresholds.…”
Section: Methodsmentioning
confidence: 99%
See 1 more Smart Citation
“…However, mosquitoes that evaded capture are likely a random sample of the overall population and are not expected to be biased toward one specific group of participants. Finally, we could not match all mosquito STR profiles to people indicating some bites may have been on individuals not enrolled in our study; however, our ability to incorporate a portion of incomplete and multisource profiles into our analysis increased our sample size by 37% 46 , allowing us to more accurately use the matched bloodmeals and human infection data to estimate potential contributions to the transmission reservoir of different groups of people. Additionally, these estimates assume equal transmission efficiency and gametocyte carriage amongst groups, which several studies have shown are also heterogeneous and nonrandom.…”
Section: Discussionmentioning
confidence: 99%
“…We genotyped human blood in both a DBS from each participant and in each mosquito abdomen classified as bloodfed for which a blood spot was available (1064/1563). We extracted gDNA from each sample type using Chelex-100, and genotyped using the Promega Geneprint 10 assay as described in Lapp et al 46 . This assay does not amplify non-human blood sources.…”
Section: Molecular Methodsmentioning
confidence: 99%